Understanding work related musculoskeletal pain: does repetitive work cause stress symptoms?. Issue 1 (21st December 2004) - Bonde, J P; Mikkelsen, S; Andersen, J H; Fallentin, N; Bælum, J; Svendsen, S W; Thomsen, J F; Frost, P; Kærgaard, A
Abstract : Background: Pain in the neck and upper extremity is reported with high frequency in repetitive work. Mechanical overload of soft tissues seems a plausible mechanism, but psychological factors have received considerable attention during the past decade. If psychological factors are important for development of regional pain in repetitive work, stress symptoms would likely be on the causal path. Aims: To examine whether objective measures of repetitive monotonous work are related to occurrence and development of stress symptoms. Methods: In 1994–95, 2033 unskilled workers with continuous repetitive work and 813 workers with varied work were enrolled. Measures of repetitiveness and force requirements were quantified using video observations to obtain individual exposure estimates. Stress symptoms were recorded at baseline and after approximately one, two, and three years by the Setterlind Stress Profile Inventory. Results: Repetitive work, task cycle time, and quantified measures of repetitive upper extremity movements including force requirements were not related to occurrence of stress symptoms at baseline or development of stress symptoms during three years of follow up. Conclusions: The findings do not indicate that repetitive work is associated with stress symptoms, but small effects cannot be ruled out. Thus the results question the importance of mental stress mechanisms in the causation of regional pain related to repetitive work. However, the findings should be interpreted with caution because the stress inventory has not been validated against a gold standard.